Perancangan Model Bisnis Telur Puyuh Steril “Ndok Gemak” Berbasis Sterilisasi Termal Untuk Segmen Rumah Tangga - Perdiyata Kurdi; Dokman Marulitua Situmorang (Politeknik Ganesha Medan, 2026)
The food and culinary sector in Indonesia continues to grow rapidly, but most culinary MSMEs still face challenges in terms of product sustainability, food safety, and market competitiveness. This research aims to design a business model for the sterilized quail egg product